Hubungan Pengetahuan Dukungan Keluarga dengan Tingkat Stress pada Pasien DM dengan Ulkus Diabetikum di Ruang Nusa Indah RSU Bhakti Asih Kota Tangerang - MH Jauhari; Ekberth Mandaku; Tanto Tanto; Reni Afriyani (Pusat Riset dan Inovasi Nasional, 2024)
Background: Diabetic ulcers are complications that occur in clients with Diabetes Mellitus (DM) due to poor glycemic control. The slow healing process of wounds can increase the risk of wound complications, which will affect the duration of healing. Objective: To determine the relationship between knowledge and family support with the level of stress in DM patients with diabetic ulcers at Bhakti Asih General Hospital in Tangerang City. Method: This is a quantitative study with a Cross-Sectional approach. The sample consists of 62 DM patients using purposive sampling technique. The instruments used in this study are questionnaires on knowledge, family support, and the Depression Anxiety Stress Scale 42 (DASS 42). Data were analyzed using Spearman's rho test and presented in the form of frequency distribution tables. Results: The findings show that the majority of the knowledge variable indicates good family support (94.9%), and the stress level variable falls into the moderate stress category (66.7%). The correlation coefficient in this study shows a significant positive correlation between knowledge and family support with the level of stress in DM patients with diabetic ulcers (r = 0.490; p = 0.001), concluding that as family support increases, the level of stress in DM patients with diabetic ulcers improves. Conclusion: There is a relationship between knowledge and family support with the level of stress in DM patients with diabetic ulcers in the Nusa Indah room at Bhakti Asih General Hospital in Tangerang City.